(untitled) (International Journal of Physiotherapy, 2020)
Background: Reasoning refers to logical thinking involving problem-solving and decision-making skills. Physical Education teachers need to manage teaching and learning processes efficiently to build reasoning ability among students. The purpose of this study was to identify the students’ reasoning achievement level based on the net and wall category using RSAT in Physical Education. Methods: A quasi-experimental design was used in this study in four schools in the district of Hilir Perak, Perak. The sample of the study consisted of 240 Form 2 students who used RSAT instrument (validity, r = .78; reliability, r = .74) in the pre-test and post-test. The treatment group underwent teaching and learning programs based on the net and wall TGfU model while the control group underwent the badminton technical model. The subjects of the control group received six teaching and learning sessions based on the plans provided. Results: The pre-test result of treatment group showed overall (M = 2.21; SD = 0.30) compared to the control group (M = 2.18; SD = 0.43). The students of the treatment group (M = 3.64; SD = 0.67) showed higher mean score compared to control group (M = 2.88; SD = 0.82) in post-test. The achievement level of the treatment group students showed that the majority of respondents achieved good level (n = 85; 60.70%) while the control group achieved pass level (n = 62; 44.30%). Conclusion: The study concluded that the use of RSAT could improve the reasoning level among students holistically and comprehensively. The implication of the study suggested an RSAT instrument to be used as an alternative instrument for determining the level of the learning domain based on reasoning to achieve higher-order thinking skills.